Flexible Pavement Design Using Bina Marga 2017 Method for The Padang Mengatas Road Section in Lima Puluh Kota Regency - Elvi Syamsuir; Hafsah Amraty; Fatma Ira Wahyuni; Ramacos Fardela (Journal of Civil Engineering and Planning (JCEP), 2024)
Kota Payakumbuh and Kabupaten Lima Puluh Kota are experiencing rapid development in the fields of economy and tourism, attracting many visitors from both local and out of town. The increase in new tourist destinations has increased traffic movement in these areas. This research was conducted to plan flexible pavement using the Bina Marga 2017 method on the Padang Mengatas road section, aiming to improve future transportation comfort and meet the increasing traffic needs, thereby supporting economic and tourism growth in the region.  This study uses a quantitative method, where the initial evaluation determines the Average Daily Traffic (ADT) and soil data (field CBR), essential information for pavement design. The research results show that the flexible pavement layer using the Bina Marga method has a CBR value of 3.1% and an ADT of 5792 vehicles per day. The recommended pavement layers consist of AC-WC with a thickness of 4 cm, AC-BC with a thickness of 6 cm, and a top foundation layer with a thickness of 40 cm.